Introductory Computer Science Course by Adopting Many Programming Languages - Zampirolli, Francisco de Assis; Teubl, Fernando; Kobayashi, Guiou; Neves, Rogério; Rozante, Luiz; Batista, Valério Ramos (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2021: Anais do XXXII Simpósio Brasileiro de Informática na Educação, 2021)
Teaching programming logic by means of a single Programming Language (PL) may lead the whole process to a particular syntax and specific libraries. In order to let every student choose their preferred PL we have developed a method that includes didactic material in many PLs by means of notebooks in Colab. We created a filter that generates Lecture Notes in different combinations of PLs from these notebooks. Moreover, each student can choose different PLs to practice with exercises and send their solutions as programming codes, which are individualized because of the parametric questions generated with MCTest+Moodle+VPL. Herewith we present our method, which is easily adaptable, validated with 5 remote classes comprising a total of 221 students, whose average pass rate was 90%.